The effects of a congested fixture period on physical performance, technical activity and injury rate during matches in a professional soccer team - Dellal, A.; Lago-Peñas, C.; Rey, E.; Chamari, K.; Orhant, E. (British Journal of Sports Medicine, 2015)
Background: In modern professional soccer, the ability to recover from official match-play and intense training is often considered a determining factor in subsequent performance.